Effects of different therapies on the lipid profile in children with juvenile idiopathic arthritis - Onufreiv, Olena; Kulchytska, Yeva-Emiliia (ScienceRise: Medical Science, 2025)
The aim of the study was to carry out a comparative effect assessment of methotrexate (MTX), adalimumab (ADA), and tocilizumab (TOC) on the blood lipid profile in children with JIA to figure out possible metabolic consequences and risks. Materials and methods: 120 patients with JIA were enrolled in the study and later divided into 3 different therapy-based groups: ADA group (n=60), TOC group (n=30), and MTX group (n=30). All patients underwent the same clinical, laboratory and instrumental evaluation, which included the disease activity assessment by JADAS27 scale and lipid profile analysis (total cholesterol (TC), low density lipoprotein cholesterol (LDL-C), high density lipoprotein cholesterol (HDL-C), very low density lipoprotein cholesterol (VLDL-C), triglycerides (TG), atherogenic coefficient (AC), both at disease onset and 3 months after reaching the pharmacological remission. Results: There were no statistically significant differences in TC, VLDL-C, and AC levels between the therapy groups at enrollment. However, the TOC group had higher TG and VLDL-C levels. All groups showed decreases in LDL-C and HDL-C levels, therefore suggesting a “lipid paradox”. Statistically significant differences were detected during remission: patients in the ADA group had a stable lipid profile with increasing HDL-C levels, whereas in the TOC and MTX groups a significant increase in atherogenic lipid parameters was seen (TC, LDL-C, TG, AC) together with a reduction in HDL-C levels. The relative incidence of dyslipidemia in remission was 33% in the ADA group, 97% in the TOC group, and 73% in the MTX group. Only in ADA group, 8.3% of patients showed regression of dyslipidemia. Spearman correlation analysis showed direct relations of JIA activity by JADAS27 with atherogenic lipids, confirming the inflammation influence on lipid metabolism even in remission. Conclusions: The results suggest that the use of different JIA therapy can significantly affect the blood lipid profile. TNF-α inhibitors helped to stabilize or even improve lipid profiles, while the therapy with tocilizumab and methotrexate was associated with the development of atherogenic dyslipidemia. This confirms the need for lipid profile monitoring in children with JIA